Quality of life in Hidradenitis Suppurativa (Acne Inversa): A scoping review - Amrit P. Kaur; Mary E. Laing; Laoise Griffin; Peter J. Carr (Wiley, 2023)
Abstract Background Hidradenitis Suppurativa (HS) is a chronic, relapsing, inflammatory skin condition which is physically, psychologically and socially disabling and often affects a patient's quality of life (QOL). There are numerous QOL tools used in dermatology. However, assessment of QOL in patients with HS is difficult due to the inability of generic QOL tools to specifically capture QOL in patients with HS. Numerous HS‐specific QOL tools have been developed in recent years. It is important to identify evidence on full psychometric evaluation of these tools. Objectives There has been a gradual increase in the use of generic and disease‐specific QOL tools in the last few decades. The aim of this scoping review (SR) is to evaluate the most widely used generic QOL tools and HS‐specific QOL tools to identify the psychometric evaluation of such tools. Methods Design: An SR guided by Joanna Briggs Institute manual and Arskey O'Malley framework guidelines. Data extraction included the studies available on full psychometric evaluation of the most widely used dermatology generic QOL tools in HS and HS‐specific QOL tools. Results Ten papers were included in the review, eight papers demonstrated HS‐specific QOL assessment tools. The psychometric properties of these tools were underpinned by reliability, validity and sensitivity measurement. Six disease‐specific tools were identified in this SR. However, they all lack full psychometric evaluation. Conclusion This review indicates that an extensive research in the field of QOL tools for HS is much needed. It is crucial to develop user‐friendly and validate disease‐specific tools to measure the real impact of disease on patients QOL. QOL instruments can evaluate the impact on life of an HS patient, thus helping improve intervention and management of disease. There is a necessity for more research into existing HS‐specific QOL tools and they should be widely tested and fully validated.